2005
DOI: 10.1200/jco.2005.08.987
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic Behavior of Gastric Adenocarcinoma in Hispanic Patients: Analysis of a Single Institution's Experience Over 15 Years

Abstract: Hispanic ethnicity does not impact survival in gastric adenocarcinoma. However, histology, metastasis pattern, tumor localization, and other clinical parameters differ sufficiently to warrant further investigation into the epidemiology, pathogenesis, and molecular biology of gastric cancer in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
73
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 67 publications
(81 citation statements)
references
References 49 publications
6
73
1
1
Order By: Relevance
“…3,5 Furthermore, a recent retrospective study from the University of Texas M. D. Anderson Cancer Center demonstrated that Hispanic patients with gastric adenocarcinoma displayed unique clinicopathologic features. 7 Although Hispanic ethnicity did not influence survival in the latter study, Asian race remained a favorable predictor of outcome. Stage migration, [8][9][10][11] treatment differences, [12][13][14] and differences in disease behavior [15][16][17][18][19] have been proposed to explain the differences in outcomes between Japanese patients and Western patients.…”
mentioning
confidence: 60%
See 3 more Smart Citations
“…3,5 Furthermore, a recent retrospective study from the University of Texas M. D. Anderson Cancer Center demonstrated that Hispanic patients with gastric adenocarcinoma displayed unique clinicopathologic features. 7 Although Hispanic ethnicity did not influence survival in the latter study, Asian race remained a favorable predictor of outcome. Stage migration, [8][9][10][11] treatment differences, [12][13][14] and differences in disease behavior [15][16][17][18][19] have been proposed to explain the differences in outcomes between Japanese patients and Western patients.…”
mentioning
confidence: 60%
“…Because our current study is representative nationally, these findings also may be attributed to the typically advanced nature of proximal tumors at presentation or to the possibility that these cancers constitute a different disease. 6,24,25 Yao et al 7 assessed the characteristics and outcome of 301 Hispanic patients with gastric adenocarcinoma among 1897 such patients who were seen at the University of Texas M. D. Anderson Cancer Center. In that study, Hispanics were more likely to be younger, to have distal tumors, and to develop peritoneal metastasis than other ethnicities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ethnic variations in disease features may be in part responsible for these results. Thus, native white Americans are at low risk, while American Indians, Blacks, and Hispanics, as well as immigrants from Russia, Scandinavia, Japan, and some Latin American countries are at high risk (10,11,(28)(29)(30)(31). From 1958 to 1979, the incidence of gastric cancer in Puerto Rican-born residents in New York City (PR-NYC) was slightly higher than in Puerto Ricans living in Puerto Rico (PR-PR), and comparable to that of other Hispanic groups that migrated to New Mexico and Los Angeles (5-9).…”
Section: Discussionmentioning
confidence: 99%